GE_GERICHTE P/11345/2011 vom 21. November 2014 - GE Cour de justice (2014)
LÉSION CORPORELLE; LÉSION CORPORELLE GRAVE; INJURE; MENACE(DROIT PÉNAL); FIXATION DE LA PEINE | CP.123; CP.177; CP.180; CP.47; CP.49